Effect of a five-week beta-alanine supplementation on the performance, cardio-respiratory system, and blood lactate level in well-trained rowing athletes: A double-blind randomized pre-post pilot study - Suszter, L.; Ihász, F.; Szakály, Z.; Nagy, D.; Alföldi, Z.; Balint, M. V.; Mák, E. (Journal of Physical Education and Sport, 2020)
Intense exercise by top-level athletes significantly lowers the pH of muscle and blood, which leads to fatigue. Beta-alanine (BA) supplementation can increase carnosine levels in skeletal muscle, which can delay a decrease in pH in the muscles. Previous studies have shown that multiple doses of BA supplementation were effective for people of different physical fitness and age. The purpose of this double-blind, randomized, controlled study is to investigate the effect of a five-week BA supplementation on well-trained, experienced rowing athletes at approximately the median dose of previous studies, which determined that 50 mg day-1 kg-1 of body weight was an effective daily dose. Two groups were formed in the spiroergometric study. One group received BA supplementation, while the control group did not. Five weeks after the first test (T1), the second test (T2) occurred, and the blood lactate levels were measured before and after the tests (Pre[La-]b; Post[La-]b). The maximum mean values of different physiological load parameters showed no significant difference. In the BA group, the mean lactate level was significantly lower after the T2 measurement (Post[La-]b) compared to those of T1 (P = 0.01) and the control group, i.e., T1 (P = 0,008), T2 (P = 0,028). The mean time and performance of the second measurement of the BA group increased [T1 = 582,7 ± 88,2 (s); T2 = 636,4 ± 106,6 (s)] but the result is not significant. In summary, the five-week dose of 50 mg/day x kg of body weight, which is 3.845/day for the group average, lowers the blood lactate levels after the tests (Post[La-]b) but does not increase the athlete's performance. For well-trained athletes, during a five-week supplementation, it is not advisable to lover the value below 4-6 g/day with the dietary supplement to achieve an ergogenic effect